A Cross-Sectional Study of Breast Cancer Surgery and the Cost Based on Data From 77 Chinese 3A Hospitals in 2015 - Zhao, Rong; Jin, Meng; Gao, Jinnan; Zhang, Linhui; Tao, Liyuan; Bao, Xiaoyuan (Frontiers in Oncology, 2022)
Purposes: We aimed to clarify the real-world status of malignant breast surgery and the cost in China. Methods: This cross-sectional survey relied on data obtained from the HSRs (Hospitalization Summary Reports) in 77 top-ranked (Grade 3A) hospitals in China to analyze breast malignant patients who underwent surgery between January 2015 and December 2015. Surgery and the cost were mainly evaluated. Results: Overall, 31900 breast malignant patients were performed surgeries in 77 hospitals. The mean age in our study was 51.5 years (SD: 11.7 years). The primary types of surgical procedures were mastectomy (n = 24629, 77.2%) and breast-conserving surgery (6210, 19.5%). The rate of mastectomy was highest at age band 50-65 (n = 10861, 82.1%) and in non-first-tier cities (n = 7651, 88.4%) as well as in North China (n = 3107, 93.2%). The rate of breast-conserving surgery was less than 10% in non-first-tier cities (9.8%), Southwest China (6.1%), and Northeast China (5.8%). The median cost was 20885.5 RMB (IQR: 15528.8-28583.5 RMB). Mastectomy cost was significantly higher than breast-conserving surgery cost both in different city tiers and regional distribution except Northeast China (p < 0.001). Conclusions: This study demonstrated the main malignant breast surgery in Chinese 3A hospitals was mastectomy, the cost varied both across and within geographic regions and city tiers. This information helps describe the real-world status of breast surgery and the cost in China.